Liquid‐liquid phase separation and fibrillation of the prion protein modulated by a high‐affinity DNA aptamer. Issue 1 (22nd November 2019) - Matos, Carolina O.; Passos, Yulli M.; do Amaral, Mariana J.; Macedo, Bruno; Tempone, Matheus H.; Bezerra, Ohanna C. L.; Moraes, Milton O.; Almeida, Marcius S.; Weber, Gerald; Missailidis, Sotiris; Silva, Jerson L.; Uversky, Vladimir N.; et al.
Abstract: Structural conversion of cellular prion protein (PrP C ) into scrapie PrP (PrP Sc ) and subsequent aggregation are key events associated with the onset of transmissible spongiform encephalopathies (TSEs). Experimental evidence supports the role of nucleic acids (NAs) in assisting this conversion. Here, we asked whether PrP undergoes liquid‐liquid phase separation (LLPS) and if this process is modulated by NAs. To this end, two 25‐mer DNA aptamers, A1 and A2, were selected against the globular domain of recombinant murine PrP (rPrP 90‐231 ) using SELEX methodology. Multiparametric structural analysis of these aptamers revealed that A1 adopts a hairpin conformation. Aptamer binding caused partial unfolding of rPrP 90‐231 and modulated its ability to undergo LLPS and fibrillate. In fact, although free rPrP 90‐231 phase separated into large droplets, aptamer binding increased the number of droplets but noticeably reduced their size. Strikingly, a modified A1 aptamer that does not adopt a hairpin structure induced formation of amyloid fibrils on the surface of the droplets. We show here that PrP undergoes LLPS, and that the PrP interaction with NAs modulates phase separation and promotes PrP fibrillation in a NA structure and concentration‐dependent manner. These results shed new light on the roles of NAs in PrP misfolding and TSEs.